Maximizing Optical Chirality Through Tailored Excitation Fields: A T-Matrix Approach - Shengzheng Qin; Hanqing Cai; Jiachen Liu; Haifeng Hu; Qiwen Zhan (Photonics)
Chiral materials are vital in various fields like physics, chemistry, and life sciences. Enhancing the interaction between light and chiral materials is crucial for advancements in these areas. We can manipulate the chirality-dependent interaction between light and materials by designing microstructural particles and tailoring incident fields. Compared to chiral photonic structures, the study of engineered optical fields is relatively underexplored, yet it has recently been recognized as a novel approach for manipulating light–matter interactions. In this study, we propose a method to design the incident field based on the T-matrix of dielectric chiral Mie spheres, aiming to maximize scattering circular dichroism. We anticipate that this approach will provide valuable insights, paving the way for predicting optimized optical chiral responses in various nanoparticles.